SPIRITUAL AND EDUCATIONAL FACTORS FOR THE DEVELOPMENT OF IDEOLOGICAL IMMUNITY IN THE YOUTH OF UZBEKISTAN - Shapsanova Nodira Berdikulovna (Journal Park Publishing, 2023)
This article shows that the need to educate young people spiritually and spiritually, to build a spirit of respect for moral and legal values, and to focus on the pursuit of maturation is an important issue. The socio-legal issue of the relevance of the creation of mechanisms for the formation of loyalty to the National idea, patriotism, high spiritual and moral views, ideological immunity, respect for legal values is covered.
Keywords: spiritual and spiritual education, morality, law, value, national idea, patriotism, high spiritual and moral views, ideological immunity, legal value, mechanism, social.